INFLUENCE OF THE 30-DAYS CENTRAL DEPRIVATION OF TESTOSTERONE SYNTHESIS ON THE MORPHOLOGICAL AND FUNCTIONAL FEATURES OF RAT TESTICULAR INTERSTITIAL ENDOCRINOCYTES AND SUSTENTOCYTES - Stetsuk, Ye.V.; Kostenko, V.O.; Shepitko, V.I.; Goltsev, A.N. (World of Medicine and Biology, 2019)
We found out that in the early stages of central deprivation of rat testosterone synthesis cells with ultrastructural signs of functional tension appeared in the population of sustentocytes and interstitial endocrinocytes, which were directed to support testicular secretion function. Central deprivation of testosterone synthesis causes the development of oxidative stress in rat testes, reduces the activity of the arginase pathway of L-arginine metabolism and changes the source of NO production from constitutive isoforms of NO synthase to inducible isoform. Identified metabolic and functional disorders of these cells lead to disorders in spermatogenesis.